Genitourinary health in a population‐based cohort of males with Duchenne and Becker Muscular dystrophies. Issue 1 (3rd June 2015) - Zhu, Yong; Romitti, Paul A.; Caspers Conway, Kristin M.; Kim, Sunkyung; Zhang, Ying; Yang, Michele; Mathews, Katherine D.; the Muscular Dystrophy Surveillance, Tracking,; Research Network
ABSTRACT Introduction: Genitourinary (GU) health among patients with Duchenne and Becker muscular dystrophies (DBMD) has not been explored using population‐based data. Methods: Medical records of 918 males ascertained by the Muscular Dystrophy Surveillance, Tracking, and Research Network were reviewed for documentation of GU‐related hospitalizations and prescribed medications. Percentages of males who received these medical interventions were calculated, and hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated for associations with sociodemographics (study site, race/ethnicity), symptoms (early‐ vs. late‐onset, ambulation status, scoliosis), and treatments (respiratory support, steroids). Results: Among the 918 males, 81 (9%) had a GU condition, with voiding dysfunction (n = 40), GU tract infection (n = 19), and kidney/ureter calculus (n = 9) most frequently seen. The Kaplan‐Meier curve produced a cumulative probability of 27%. Cox regression showed GU conditions were more common when males were non‐ambulatory (HR 2.7, 95% CI 1.3–5.6). Conclusions: Our findings highlight the need for increased awareness of GU health and multidisciplinary care of DBMD patients. Muscle Nerve52: 22–27, 2015